O impacto da covid-19 na comercialização e no consumo de animais silvestres: um estudo sobre segurança alimentar e nutricional em tempo de pandemia no município de Abaetetuba/PA - Costa, Tayara Silva (Universidade Federal do Pará, 2024)
It is known that wild animals and their by-products continue to be handled in different cultures and societies, especially as the basis of the human diet. In this way, the present work aims to characterize the impact of the COVID-19 pandemic on the trade of wild fauna and its by-products intended for food, analyzing whether consumers associate game meat with the contagion of the new coronavirus and, consequently, if they believe that frequent consumption of wild animals can threaten Food and Nutritional Security in the city of Abaetetuba/PA. The field period was between September 2019 and November 2020, with some gaps between visits to Abaetetuba. The main instruments of the methodology used were semi-structured interviews in loco and a questionnaire registered via the internet. There was no collection of biological material, this verification being the responsibility of the photographic record and the specific literature. As a result of the investigation, it can be seen that the free fair of the "beira" of Abaetetuba still represents a place of preservation of social and cultural relations, which strengthen affective ties and local knowledge. In it, there is an extensive network of relationships in which the commercialization of wild animals remains rooted in a chain of affinities that characterize the local sociocultural and symbolic identity, in addition to representing an important source of income and/or economic complement. The emergence of the COVID-19 pandemic impacted, to a certain extent, the trade and consumption of wild animals, since, with the low supply of animal protein at the fair and the increase in domestic meat (cattle, chicken, pork...), there was an increase in the consumption of game meat, even though the price of this has also been high in the pandemic period. Game meat has become a cheaper, healthier and more durable alternative (salted). Thus, many consumers said they did not associate the contagion of COVID-19 with the consumption of bushmeat, as well as they did not believe that the frequent consumption of wild animals could threaten Food and Nutrition Security in the municipality.